A high linoleic acid diet exacerbates metabolic responses and gut microbiota dysbiosis in obese rats with diabetes mellitus. Issue 2 (23rd January 2019) - Lee, Hsiu-Chuan; Yu, Shao-Chuan; Lo, Yun-Chun; Lin, I-Hsuan; Tung, Te-Hsuan; Huang, Shih-Yi
Abstract : Dietary polyunsaturated fatty acid (PUFA) levels may affect inflammatory responses and lipid metabolism. Abstract : Dietary polyunsaturated fatty acid (PUFA) levels may affect inflammatory responses and lipid metabolism. Gut microbiota diversity is strongly associated with chronic inflammatory disease, diabetes mellitus (DM), and obesity through abnormal energy homeostasis. In this study, the association between metabolic responses and gut microbiota diversity at different dietary n-6/n-3 PUFA ratios was evaluated in DM rats. Obesity and DM were induced in rats by using a high-fat diet and streptozotocin (STZ), respectively. The obese DM rats were assigned to three groups and administered regular (R), high (H), and low (L) n-6/n-3 ratio diets (n-6/n-3 = 6.39, 3.02, and 9.29, respectively) for 6 weeks. Some metabolic parameters and gut microbiota of the rats were analysed. The results revealed that a high linoleic acid diet increased the plasma and kidney interleukin 6 levels, whereas a low n-6/n-3 ratio diet ameliorated blood glucose homeostasis, reduced plasma tumour necrosis factor α levels, and inhibited systematic inflammation. DM rats exhibited low gut microbiota diversity; however, compared with the R group, the L and H groups did not exhibit alterations in the α-diversity (Observed, Chao 1, Shannon and Simpson). The percentage of Firmicutes was lower in the DM groups than in the non-DM group; however, the L group showed a nonsignificantly higher Firmicutes / Bacteroidetes ratio than did the other groups. Thus, a low n-6/n-3 ratio diet can improve blood glucose homeostasis, reduce systematic inflammation, ameliorate glomerular basal membrane thickening, reduce the expression of receptors of advanced glycation end products in renal vessel walls, and prevent diabetic nephropathies.